Measuring the Service Quality of Tehran Medical Centers Of Martyrs And Veteran Affairs Foundation - Gh. Tabarsa; A. Ahmadizad (Afarand Scholarly Publishing Institute, 2011)
Purpose: In order To Achieve Better Services , We need to know of Veterans' satisfaction from Medical Centers Of Martyrs And Veteran Affairs Foundation. Method & Materials: This Study is A Descriptive & Survey research. Its Statistical Population are Veterans of Tehran city in 1389. The random sampling with a sample size of 149 members is used and then , 145 questioners are confirmed. descriptive and inferential statistics are applied for analysis. Results: This research shows that the satisfaction of Veterans in four indices including Assurance, Reliability, Responsiveness and empathy are suitable but Tangibles unsuitable Conclusion: We Suggest intangible assets were improved more than other indices, However the quality of other indices were improved